Focus on grammar : workbook. A high-intermediate course for reference and practice - Fuchs,Marjorie; Lê Huy Lâm; Bonner, Margaret (Tp.HCM : Nxb Tp.HCM, 1997)
Present and past; Future; tag question, additions, and responses; gerund and infinitves; Passive; Modals;conditionals; adjective clauses...
Keywords: English language; English Grammar; English language -- Grammar